연안환경개선방안 - 신광선 (The Graduate School, Ajou University, 2014)
Ocean became the marshaling area of water pollutants. Sea flotsam occur lot of environmental problem which pollutes ocean and fish and shellfish caught in the waste fishing net and even waste fishing net get caught in boat screw its make another accident. The root cause of ocean pollutants has land and ocean way following inflow route. The pollutants from land cause by waste from land people and trashes during heavy rain and typhoon. The pollutants from ocean cause by waste from boats which fish man’s utilities like fishing gears. Korea which surrounded by 3 side of sea and ocean pollutants are found in most of seas. The amount of annual ocean pollutants is around 159,000 ton in Korea. The result of collecting deposited waste in 15 districts indicates obstacle 64.9%, precipitate 34.7%, floaters 0.4%. It is essential to create obstacle decreasing methods in The East Sea because collected obstacles of The East Asia were the largest in quantity. After collecting deposited waste, study showed 5% improvements of COD in 15 districts. It means that it is necessary to collect deposited waste consistently to improve environment. To obtain accurate and reliable data, It is important to identify investigation conditions such as time of investigation point When evaluating the effects, It appears that adding ecology-based water quality criteria and ecological item such as benthic organism can make investigation more reliable.
학위논문(석사)--아주대학교 산업대학원 :환경공학과,2014. 8
Keywords: 환경